2008
DOI: 10.1007/s11418-008-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anti-inflammatory and hepatoprotective potency of Polyalthia longifolia var. pendula leaf in Wistar albino rats

Abstract: The objective of the present study was to screen various solvent extracts of Polyalthia longifolia var. pendula (Annonaceae) leaf for anti-inflammatory activity and to evaluate the anti-inflammatory and hepatoprotective potency of the potent solvent extract. Successive extraction was performed with six different solvents, viz. petroleum ether, hexane, toluene, chloroform, acetone and methanol. Toluene, chloroform, acetone and methanol were used in acute inflammatory studies; the results revealed methanol as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…As it is noted that natural products and their semi-synthetic derivatives are potentially safer and more active than the synthetic compounds 19,20 , the metabolites from natural sources are extensively screened for their dual inhibitor properties. Several previous studies 21,22 have demonstrated good in vivo anti-inflammatory activities of Polyalthia longifolia (Family: Annonaceae) extracts. However, the specific metabolites that are responsible for this activity and the proper enzymatic investigations against COX-1, COX-2, and 5-LOX remained undetermined.…”
Section: -Lipoxygenase (5-lox)mentioning
confidence: 95%
“…As it is noted that natural products and their semi-synthetic derivatives are potentially safer and more active than the synthetic compounds 19,20 , the metabolites from natural sources are extensively screened for their dual inhibitor properties. Several previous studies 21,22 have demonstrated good in vivo anti-inflammatory activities of Polyalthia longifolia (Family: Annonaceae) extracts. However, the specific metabolites that are responsible for this activity and the proper enzymatic investigations against COX-1, COX-2, and 5-LOX remained undetermined.…”
Section: -Lipoxygenase (5-lox)mentioning
confidence: 95%
“…pendula (Annonaceae) is a tall evergreen tree cultivated all over India. The plant has been used in the traditional system of medicine for the treatment of fever, skin diseases, hypertension (Kirtikar & Basu, 1995), hepatoprotective, anti-inflammatory (Tanna et al, 2009), antimicrobial (Faizi et al, 2003;Murthy et al, 2005;Nair & Chanda, 2006), hypoglycemic and antihyperglycemic (Nair et al, 2007) and antiulcer activities (Malairajan et al, 2008). Polyalthia cerasoides (Roxb.)…”
Section: Research Articlementioning
confidence: 99%
“…In another study, the ethanolic and aqueous extracts of P. longifolia were found to reduce Carrageenan induced edema and inflammation [18]. Hepatoprotective potential of plant has also been demonstrated in an animal study [19,20].…”
Section: Introductionmentioning
confidence: 89%